Outcome of decompression, correction and fusion for cervical spondylotic myelopathy with kyphotic deformity - Islam, M. Anowarul; Saha, Asim Kumar; Fahim, Zafri Ahmed; Islam, Afia Ibnat; Aziz, Sanjida; Das, Pinto Chandra (International Journal of Research in Medical Sciences, 2025)
Background: Cervical spondylotic myelopathy (CSM) with kyphotic deformity is a common degenerative spinal disorder that leads to progressive spinal cord compression and neurological deterioration. Objectives were to evaluate the outcome of decompression by laminectomy with correction by lateral mass fixation and fusion for CSM with kyphotic deformity. Methods: Assessments were done pre-operatively and postoperatively at 1-, 2-, 3-, and 6-months using visual analogue score (VAS), modified Japanese orthopedic association (mJOA), Odom criteria, Nurick’s grading, and cervical curvature index. Data were analyzed using standard statistical methods via the statistical package for social sciences (SPSS) version 25 (IBM®, Armonk, USA). A p<0.05 was considered statistically significant. Results: The mean VAS score significantly improved from 6.27±1.75 to 0.73±0.59 at 6 months. The mean mJOA score increased from 11.27±0.80 preoperatively to 16.53±0.74 at the final follow-up, indicating substantial neurological improvement. According to the modified Odom criteria, 33.3% of patients had excellent outcomes, 60.0% had good outcomes, and 6.7% had fair outcomes. Functional status measured by Nurick’s grading improved significantly, with 93.3% of patients in grade III preoperatively and 100% improving to either grade 0 or I by 6 months (p<0.001). The cervical curvature index showed marked radiological correction, improving from -8.24±2.59 preoperatively to 21.94±1.35 postoperatively (p<0.001). Conclusions: Posterior decompression by laminectomy with lateral mass fixation and fusion is an effective and safe surgical technique for managing CSM with kyphotic deformity. It significantly improves neurological function, pain status, and cervical alignment.